Immune Mediated Degeneration and Possible Protection in Glaucoma - Tsai, Teresa; Reinehr, Sabrina; Maliha, Ana M.; Joachim, Stephanie C. (Frontiers in Neuroscience, 2019)
The underlying pathomechanisms for glaucoma, one of the most common causes of blindness worldwide, are still not identified. In addition to increased intraocular pressure (IOP), oxidative stress, excitotoxicity, and immunological processes seem to play a role. Several pharmacological or molecular/genetic methods are currently investigated as treatment options for this disease. Altered autoantibody levels were detected in serum, aqueous humor, and tissue sections of glaucoma patients. To further analyze the role of the immune system, an IOP-independent, experimental autoimmune glaucoma (EAG) animal model was developed. In this model, immunization with ocular antigens leads to antibody depositions, misdirected T-cells, retinal ganglion cell death and degeneration of the optic nerve, similar to glaucomatous degeneration in patients. Moreover, an activation of the complement system and microglia alterations were identified in the EAG as well as in ocular hypertension models. The inhibition of these factors can alleviate degeneration in glaucoma models with and without high IOP. Currently, several neuroprotective approaches are tested in distinct models. It is necessary to have systems that cover underlying pathomechanisms, but also allow for the screening of new drugs. In vitro models are commonly used, including single cell lines, mixed-cultures, and even organoids. In ex vivo organ cultures, pathomechanisms as well as therapeutics can be investigated in the whole retina. Furthermore, animal models reveal insights in the in vivo situation. With all these models, several possible new drugs and therapy strategies were tested in the last years. For example, hypothermia treatment, neurotrophic factors or the blockage of excitotoxity. However, further studies are required to reveal the pressure independent pathomechanisms behind glaucoma. There is still an open issue whether immune mechanisms directly or indirectly trigger cell death pathways. Hence, it might be an imbalance between protective and destructive immune mechanisms. Moreover, identified therapy options have to be evaluated in more detail, since deeper insights could lead to better treatment options for glaucoma patients.